In vitro 3D skin culture and its sustainability in toxicology: a narrative review - Syafira Masri; Mh Busra Fauzi; Nor Fadilah Rajab; Wing-Hin Lee; Diana Atiqah Zainal Abidin; Ee Ling Siew (Artificial Cells, Nanomedicine, and Biotechnology)
In current toxicological research, 2D cell cultures and animal models are well- accepted and commonly employed methods. However, these approaches have many drawbacks and are distant from the actual environment in human. To embrace this, great efforts have been made to provide alternative methods for non-animal skin models in toxicology studies with the need for more mechanistically informative methods. This review focuses on the current state of knowledge regarding the in vitro 3D skin model methods, with different functional states that correspond to the sustainability in the field of toxicology testing. We discuss existing toxicology testing methods using in vitro 3D skin models which provide a better understanding of the testing requirements that are needed. The challenges and future landscape in using the in vitro 3D skin models in toxicology testing are also discussed. We are confident that the in vitro 3D skin models application may become an important tool in toxicology in the context of risk assessment.